Properties of Lintnerized Starch Granules From Rices Differing in Amylose Content and Gelatinization Temperature - Maniñgat, C.C.; Juliano, Bienvenido O. (Wiley, 1979)
A study was made on the properties of starch granules of eight rices differing in amylose content and gelatinization temperature subjected to hydrolysis in 2.2‐N HC1 at 35°C for 15 days. The recovery of lintnerized starch was greater for samples with high gelatinization temperature and, to a lesser extent, high amylose content. Lintnerized starch had sharper X‐ray diffraction peaks than native starch. Their DP ranged from 18.8 to 30.3 glucose units, and the β‐amylolysis limit ranged from 74.5 to 92.1%. Gel chromatography showed two peaks corresponding to DP 29–34 and 14–7. Varietal differences were noted in the ratio of the two amylodextrin peaks.